FIQH AL-LUGHAH DALAM BAHASA ARAB: DEFINISI, PERKEMBANGAN, METODE DAN OBJEK KAJIAN - D. Hidayat; Ikhwan Nugraha (LPPM STAI Nida El-Adabi, 2022)
Arabic is always interesting to discuss as an object. This is none other than because the Al-Quran and Hadith came down in Arabic, and also because the Prophet Muhammad was an Arab who was fluent in Arabic (afshahul lisan) and had many poems and stories in Arabic. Over time, the study of Arabic has expanded and become a separate scientific discipline that is separate from its main science. Interestingly, many are often stuck with terms in Arabic science because of the mixture that is almost impossible to distinguish, for example between fiqh al-lughah (often called philology) and al-lughah science (linguistics). The purpose of this research is to explain fiqh al-lughah in Arabic, which is different from the science of al-lughah. starting from the definition, development, method, and object of study. This research is qualitative with a library research approach and uses descriptive analysis. The results of this study indicate that fiqh al-lughah belongs to the realm of knowledge (ma'rifah) and is not a science such as nahw or balaghah. There are important points related to the study of fiqh al-lughah that are different from other linguistics; maybe even fiqh al-lughah only exists in Arabic. This has an impact on the development of studies related to Arabic, especially the Koran and hadith, which causes a variety of interpretations to emerge.